Amorphous iron(III) oxide--a review - Machala, Libor; Zboril, Radek; Gedanken, Aharon (The journal of physical chemistry. B, 2007)
The syntheses of amorphous Fe(2)O(3) nanoparticles of varying size and morphology, their magnetic properties, crystallization mechanism, and applications are reviewed herein. The synthetic routes are classified according to the nature of the sample (powders, nanocomposites, films, coated particles). The contributions of various experimental techniques to the characterization of an amorphous Fe(2)O(3) phase are considered in this review, including some key experimental markers, allowing its distinction from nanocrystalline "X-ray amorphous" polymorphs (maghemite, hematite). We discuss the thermally induced crystallization mechanisms depending on transformation temperature, atmosphere, and the size of the amorphous particles that predetermine the structure of the primarily formed crystalline polymorph. The controversial description of the magnetic behavior, including an interpretation of the low-temperature and in-field Mössbauer spectra, is analyzed.